The raised fourth in Leonard Bernstein’s West Side Story - Viljoen, Nicol; Visagie, Johann (University of the Free State, 2010)
This article traces the functions and applications of the raised fourth-scale degree in Leonard Bernstein’s West Side Story against the background of the work’s precarious positioning between a Broadway musical and a modern opera. It attempts to demonstrate how the raised fourth operates in a variety of ways as a coherent tonal motive with distinctive tragic undertones. While it relates the main songs and musical sequences to one another, it also effects a poignant relationship between the lyrics, music and dramatic action. In this regard it represents a powerful instance of musical symbolism, its tragic quality being closely intertwined with the story’s disturbing theme of gangsterism.

Hierdie artikel ondersoek die funksies en toepassings van die verhoogde vierde toontrap in Leonard Bernstein se West Side Story teen die agtergrond van die werk se dubbelslagtige posisionering tussen ’n Broadway musiekblyspel en ‘n moderne opera. Dit trag om aan te toon hoe die verhoogde vierde op verskeie wyses as ’n koherente tonale motief met kenmerkende tragiese ondertone optree. Terwyl dit die belangrikste liedjies en musikale sekwense met mekaar verbind, bewerkstellig dit terselfdertyd ’n kragtige aanwending van musikale simboliek, waarvan die tragiese kwaliteit ten nouste met die storie se ontstellende tema van gangsterisme verweef is.
Keywords: Bernstein, Leonard; West Side Story; Musical symbolism; Gangsterism; Broadway musicals; Opera